Good Jew, bad Jew racism, anti-semitism and the assault on meaning - Friedman, Steven (Wits University Press, 2023)
"Political theorist Steven Friedman addresses how and why the current language around anti-Semitism in Israel has been distorted and weaponised to serve the political objectives of the Israeli state. Friedman's critique examines what this implies for the fight against racism in South Africa and India, and in other parts of the world."
Keywords: Rassismus; Sprachgebrauch; Antisemitismus; Südafrika; Israel; Antisemitism; Jews / Identity; Racism